Efficacy of removable rigid dressing after transtibial amputation in diabetes mellitus patients (Faculty of Medicine Universitas Indonesia, 2013)
Background: The aim of this study was to evaluate the RRD’s efficacy in decreasing stump edema and pain compared to elastic bandage for diabetic mellitus patients after transtibial amputation. Methods: Interventional research was using consecutive sampling. Subjects were randomized into two groups: RRD and elastic bandage. Twenty-three subjects were analyzed. Stump edema volume was measured by the amount of water spilled out from volume glass. Elastic bandage was reapplied every 4 hours and RRD was refitted every 7 days during evaluation time. Stump edema volume was evaluated every 7 days during the 8 week observation. Results: There was a significant decrease of stump volume in RRD group during the first and second week (p = 0.03, p = 0.01) and the edema decreasing time was also significant (p = 0,03). The average decrease of edema volume in RRD was 63.85% of second week and in the elastic bandage group was 34.35%. There were a tendency of pain reduction time in RRD group (4.83 ± 1.95 weeks) compared to elastic bandage group (5.18 ± 2.31weeks). Cox regression result of decreasing edema volume time was 3.088 (CI 95%: 1.128 – 4.916). Conclusion: This study found that there was stump edema volume acceleration in RRD group, it was three times faster for stump to become not edematous compared to elastic bandage group. There was a tendency of faster decreasing stump pain in RRD group than elastic bandage group, eventhough this result was not statistically significant. (Med J Indones. 2013;22:16-21) Keywords: Diabetes mellitus, removable rigid dressing, transtibial amputation